Transovarial Transmission of Dolichos Yellow Mosaic Virus by Its Vector, Bemisia tabaci Asia II 1 - Ghosh, Amalendu; Roy, Buddhadeb; Nekkanti, Aarthi; Das, Amrita; Dhar, Shri; Mukherjee, Sunil Kumar (Frontiers in Microbiology, 2021)
The cultivation of dolichos bean has been severely affected by dolichos yellow mosaic virus (DoYMV, Begomovirus). DoYMV is transmitted by whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae). The present study provides the first evidence of transovarial transmission and propagation of a bipartite begomovirus in its vector, B. tabaci Asia II 1. We have tested the transovarial transmission of DoYMV in next-generation B. tabaci by PCR, real-time PCR, Southern blot hybridization, and biological transmission. The eggs, laid by DoYMV-exposed B. tabaci, carries the virus in a unique pattern. Only the eggs laid in between 3-6 days post virus acquisition by a parent B. tabaci were DoYMV positive. When tested individually in real-time PCR, around 31-53% of eggs carried the viral DNA. Presence of the DoYMV in ovaries and F1 eggs was further substantiated by hybridization of a Cy3-conjugated nucleic acid probe complementary to the viral strand of DoYMV. Viral DNA was also detected in F1 adults and F2 eggs. B. tabaci progenies carried not only the DoYMV DNA but were also infective. The F1 adults transmitted DoYMV to all tested plants and produced strong yellow mosaic symptoms. An increase in viral copies from egg to nymphal stage indicated propagation of DoYMV in B. tabaci. However, the increase was for a short period and decreased thereafter. The transovarial transmission and replication of DoYMV in B. tabaci have great epidemiological relevance as B. tabaci can serve as a major host of the virus to bridge the gap between the cropping seasons.